Studi Literatur: Implementasi Evaluasi Program Pendidikan Anak Berkebutuhan Khusus di Sekolah-Sekolah Inklusi di Indonesia - Wijaya, Muhammad Yudhistira (Arden Jaya Publisher, 2024)
Like regular children in general, children with special needs (ABK) also have the right to receive the same educational rights. In the ABK education process, there is inclusive education which is useful for facilitating the learning process in public schools without discrimination. ABK learning in public schools is adjusted to the abilities and characteristics of each student. For this reason, choosing an effective and efficient learning implementation is necessary for students to achieve learning goals and will of course help ABK later in achieving optimal development and success in life. Apart from that, evaluation of ABK education in inclusive schools is very necessary for continuous improvement in order to realize better inclusive education for all. The purpose of writing this article is to describe the various learning implementations implemented in inclusive classes during teaching and learning activities, how these learning implementations are implemented and the inhibiting and supporting factors in teaching and learning activities in inclusive schools. The method used in writing articles uses library research techniques and reference sources taken from scientific articles and electronic news that have been published.